FRI0441 Idiopathic inflammatory myopathies: clinical characteristics, survivial and poor prognostic factors of 110 patients from turkey. (12th June 2018) - Oguz, E.; Erdugan, M.; Esen, B.A.; Gul, A.; Ocal, L.; Inanc, M.
Abstract : Objectives: In this study, we aimed to assess clinical features, poor prognostic factors and survival analysis of patients with Idiopathic inflammatory myopathy (IIM). Methods: Records of 110 patients with IIM that had at least 6 months of follow-up, fulfilling Bohan and Peter's criteria were analysed for this study. Survival analysis was done by using Kaplan Meier method and multiple "Cox" regression analysis was applied to calculate the effect of multipl factors. Results: Sixty-eight percent of 110 patients was female, the mean age of the patients was 46 years, and the average follow up time was 77.5 months. Diagnosis of these patients was dermatomyositis (DM) in 68%, polymyositis (PM) in 26%, autoimmune necrotizing autoimmune myopathy (NOM), inclusion body miyositis (IBM) 6%. The percentage of periungual erythema, arthritis, dysphagia, respiratory muscle involvement and interstitial lung disease(ILD) 56, 22, 24, 32, 11 and 30. Malignancy was identified in 26% of patients. The percentages of malignancies diagnosed at the time of diagnosis, before the diagnosis and during the follow-up were 3.6, 11.8 and 8.2. The most frequent malignancy was breast cancer. Others are carcinoma of gastrointestinal tract, lung, and genitourinary tract. ANA was present in 36% and 12% of patients was positive for anti-Jo-1 antibody. The average daily dose of prednisolone was 7.5 mg, the average usage time was 35.5 months. Causes of death were aspiration pneumonia-sepsis (50%) and malignancy (25%). Significant associations with mortality was found between systemic symptoms, periungual erytema, respiratory muscle involvement, dysphagia, presence of malignancy. Mortality was higher in ANA negative patients (p<0.001), Five and 10 year survival in these patients were 83% and 75%. Five year survival rate in patients with respiratory muscle involvement was 38% and 68% in those with dysphagia. The presence of systemic symptoms, and malignancies were identified as risk factors for mortality in multivariable analysis. Conclusions: ILD and malignancies are frequent in our IIM cohort. Malignancies are mostly detected at diagnosis. The mortality rate was high and the most common cause was infection. 10 year survival rate was 79%. Malignancy, respiratory muscle involvement, dysphagia, negative ANA have a detrimental effect survival in IIM patients. Disclosure of Interest: None declared